2014
DOI: 10.1107/s1600576714016896
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved coherent X-ray diffraction imaging of surface acoustic waves

Abstract: Time-resolved coherent X-ray diffraction experiments of standing surface acoustic waves, illuminated under grazing incidence by a nanofocused synchrotron beam, are reported. The data have been recorded in stroboscopic mode at controlled and varied phase between the acoustic frequency generator and the synchrotron bunch train. At each time delay (phase angle), the coherent far-field diffraction pattern in the small-angle regime is inverted by an iterative algorithm to yield the local instantaneous surface heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…Subsequently we observe oscillations of the diffracted intensity with a period of T SAW = 1310 ps. Due to the short x-ray penetration depth in our surface diffraction experiment, we rely on kinematic theory [31][32][33][34] and find the following expression for the diffracted intensity from a PSE under grazing incidence below the critical angle α i < α c :…”
mentioning
confidence: 99%
“…Subsequently we observe oscillations of the diffracted intensity with a period of T SAW = 1310 ps. Due to the short x-ray penetration depth in our surface diffraction experiment, we rely on kinematic theory [31][32][33][34] and find the following expression for the diffracted intensity from a PSE under grazing incidence below the critical angle α i < α c :…”
mentioning
confidence: 99%
“…Typically, experiments employ an optical laser pulse which is diffracted from the excited modes via photothermal or photoelastic effects [28,29]. Alternatively, PSDs can be detected using x-ray diffraction and photoemission electron microscopy techniques [30][31][32]. We have recently shown that the PSD associated with the excited quasi-static and transient modes may also be probed by TR-XRR [14,15].…”
Section: Coherent Control Of Periodic Surface Deformationsmentioning
confidence: 99%
“…Surface acoustic waves (SAWs) have been previously observed with frequency-matched synchrotron X-ray scattering, historically with diffraction micro-topography [18,19], more recently with iterative phase retrieval of surface topography utilizing SAW satellite peaks [20,21], and also with photoemission electron microscopy tech-niques [22,23]. These methods have typically utilized full field x-ray illumination with microscopic contrast mechanisms sensitive to a scalar projection of the lattice curvature at spatial resolutions down to 100 nm.…”
mentioning
confidence: 99%